Атлас мира для школьника: [перевод с английского] / Ф. Стил - Стил Филип (Олма-Пресс, 2002)
Экземпляры: ф.5 (2002) / Инвентарный номер: 44549 / Цена: / Сис.шифр: 26.8я6 / Авт.знак: С 80 / ГРНТИ: 39.21 / ББК: 26.89(0)я6